2010
DOI: 10.1038/cgt.2010.5
|View full text |Cite
|
Sign up to set email alerts
|

Potent antitumor effects of combined therapy with a telomerase-specific, replication-competent adenovirus (OBP-301) and IL-2 in a mouse model of renal cell carcinoma

Abstract: OBP-301 (a telomerase-specific, replication-competent adenovirus with hTERT promoter) was constructed in a previous study and it showed a strong anticancer effect by inducing cell lysis in human lung and prostate cancer cells. This study investigated the effectiveness of a combination therapy of OBP-301 and interleukin-2 (IL-2) in a mouse model of renal cell carcinoma (RCC). The cell-killing effect of OBP-301 was confirmed in vitro in the RENCA cancer cells. In in vivo experiment, luciferase-expressing RENCA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Therefore, targeting the catalytic subunit hTERT represents a promising approach for diminishing telomerase function that will probably not cause substantial side effects on telomerase‐negative somatic cells . Development of hTERT‐based probes has broad implications in oncology studies, such as clinical diagnosis, staging, therapy, monitoring therapeutic responses, and in biomedical research …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, targeting the catalytic subunit hTERT represents a promising approach for diminishing telomerase function that will probably not cause substantial side effects on telomerase‐negative somatic cells . Development of hTERT‐based probes has broad implications in oncology studies, such as clinical diagnosis, staging, therapy, monitoring therapeutic responses, and in biomedical research …”
Section: Introductionmentioning
confidence: 99%
“…The human telomerase reverse transcriptase (hTERT) promoter has been well characterized and determined to be available for cancer tissue-specific gene expression in a broad range of malignant tissue types (1)(2)(3). In previous studies, we have demonstrated that treatment with an hTERT-driven replication competent adenovirus, OBP-301, led to significant tumor regression in mouse models of prostate and renal cancer (4,5). However, the in vivo use of tissuespecific promoters, including hTERT, is often limited because the specific promoters can not lead to sufficient levels of therapeutic or reporter gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptional regulation of transgene expression using tumor‐ or tissue‐specific promoters within adenoviral vectors has already been attempted to treat tumors 7, 8. However, only a limited number of promoters that restrict gene expression to RCC have been studied 9–11 because clinically defined RCC tumor markers whose promoter is highly active in tumors but either silent or active at very low background levels in normal kidney cells are not available. Therefore, the development of a novel inducible promoter system that allows reliable and controllable transactivation of ectopic gene expression in restricted tissue or cell types by administration of inducing agents is essential for the success of a RCC targeted gene therapy that does not induce serious kidney damage.…”
Section: Introductionmentioning
confidence: 99%